A Judicial Cure for the Disease of Overcriminalization - Smith, Stephen F. (2014)
The dangers of “overcriminalization” are widely appreciated across the political spectrum, but confusion remains as to its cause. Standard critiques fault legislatures alone. The problem, however, is not simply that too many criminal laws are on the books, but that they are poorly defined in ways that give unwarranted sweep to the criminal law, raising the danger of punishment absent or in excess of moral blameworthiness. Instead of narrowing ambiguous criminal laws to more appropriate bounds, courts frequently expand them, even when this ratchets up the punishment that offenders face, and fail to insist on proof of sufficiently culpable states of mind to render the resulting punishment just. By changing how they interpret criminal statutes, taking narrow construction principles and state-of-mind requirements more seriously, courts can help to cure the over criminalization disease